FAKTOR – FAKTOR YANG MEMPENGARUHI KESADARAN BERINFAQ PADA JAMA’AH SHOLAT JUM’AT DI MASJID KELURAHAN SIDOMULYO TIMUR KOTA PEKANBARU (STUDI KORELASI) - Rusmita "; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this study was to determine the factors that influence the awareness of giving infaq and to analyze the correlation between the factors that influence the awareness or behavior of giving infaq to the congregation of Friday prayers at the Sidomulyo Timur mosque, Pekanbaru City. This type of research is quantitative descriptive. The population in this study is the community in the Kelurahan Sidomulyo Timur, Pekanbaru City in giving infaq every Friday, while the sample in this study amounted to 100 people with the pruposive sampling method. Data analysis using person product moment correlation. The results of the study explain that religious factors, knowledge, income and the role of ulama have a significant relationship to the awareness of the congregation in giving infaq at the mosque, in the East Sidomulyo Village, Merpoyan Damai District, Pekanbaru City. Keywords : Religion, Knowledge, Income, Role of Ulama and Awareness of Giving.